CHARACTERIZATION OF GREEN-SYNTHESIZED COBALT OXIDE NANOPARTICLES USING Nigella sativa SEED EXTRACT - Hizkia Alpha Dewanto; Sarah Toding; Irfan Riadin; Jatmoko Awali; Andi Idhil Ismail; Fredy Kurniawan; Yosua Anjupaian Situmeang; Yunita Triana (Universitas Mataram, 2026)
Cobalt oxide nanoparticles (CoO NPs) were synthesized via green synthesis using Nigella sativa seed extract as a natural reducing and stabilizing agent. This approach enables environmentally friendly production of ultrafine nanoparticles while incorporating bioactive plant compounds. The CoO NPs were characterized using XRD, XRF, UV–Vis, FTIR, and TEM. XRD confirmed CoO formation with diffraction peaks at 2θ = 31.247°, 36.712°, 42.5°, 44.771°, 59.359°, 61.536°, 65.227°, 74.31°, and 76.111°, which are indexed to the (100), (111), (200), (102), (110), (103), (220), (311), and (222) planes of face-centered cubic (fcc) CoO. XRF showed cobalt as the main element (71.36 wt%) with minor P, S, K, Ca, Fe, Zn, Cu, Mn, and Ti. UV–Vis exhibited peaks at 320 nm and 344 nm, TEM revealed nearly spherical particles (1.72 nm with a standard deviation of 0.55 nm), and FTIR confirmed Co–O bonds (700–663 cm⁻¹) along with organic functional groups from the extract. The formation mechanism involves phytochemical-mediated bioreduction, surface stabilization, and producing well-dispersed CoO NPs. Overall, all characterization techniques consistently confirm the successful formation of highly crystalline, pure, and well-dispersed CoO nanoparticles with nanoscale dimensions. The combined results demonstrate that Nigella sativa extract effectively acts as both reducing and stabilizing agent, leading to stable CoO NPs suitable for potential applications in catalytic and functional material systems.